GNB2L1 and its O-GlcNAcylation regulates metastasis via modulating epithelial-mesenchymal transition in the chemoresistance of gastric cancer. - Shimeng Cheng; Qiqi Mao; Yabing Dong; Jie Ren; Lina Su; Jianlan Liu; Qingmei Liu; Jing Zhou; Xiaolu Ye; Shudan Zheng; Ningwen Zhu (PLoS ONE)
GNB2L1 and its O-GlcNAcylation has been reported to play roles in gastric cancer metastasis. However, the roles of GNB2L1 in chemoresistance of gastric cancer has never been determined. In the present study, we found that GNB2L1 was downregulated in chemoresistant patients of gastric cancer, and observed the decrease of GNB2L1 in protein levels instead of mRNA levels in different chemoresistant gastric cancer cell lines. Further we proved that this downregulation of GNB2L1 was resulted from its elevated O-GlcNAcylation catalyzed by OGT in both cell lines and patients. Next, we investigate the function of GNB2L1 and its O-GlcNAcylation on gastric cancer metastasis during chemoresistance, and confirmed Ser124 as the major O-GlcNAcylation site on GNB2L1 that regulated its function on metastasis. Furthermore, our data demonstrated that GNB2L1 modulated EMT via regulating the translation of EMT-related proteins in the process of chemoresistance. In summary, this study indicated that GNB2L1 and its O-GlcNAcylation regulated metastasis via modulating the translation of EMT-related proteins in the chemoresistance of gastric cancer.